Avaliando resultados de um programa de transferência de renda: o impacto do Bolsa-Escola sobre os gastos das famílias brasileiras - Anne Caroline Costa Resende (2006)
The aim of this work is to analyze the effects of cash transfers of public programs on households expenditures and their components, taking the Brazilian program Bolsa-Escola as a representative example. Many methodological possibilities are explored and compared using different matching estimators, in an attempt to enhance the understanding of non experimental methods.To achieve such objectives, it is used a non experimental method called propensity score matching. The aim of the matching is to find an ideal group of comparison for the treatment group from a sample of non participants, based on observable characteristics. From that point, the average treatment effect on treated can be computed by using distinct non parametric matching algorithms. It is used microdata from the Pesquisa de Orçamentos Familiares (POF) 2002-2003. Further, a sensibility analysis is made to certify that the propensity score model is well specified and still works in the presence of unobservable variables.Results suggest a positive effect of money transfers on the poor beneficiary households consumption. The fact that households expenditures are concentrated on education, hygiene products, clothing and general food instead of drinks, cigarettes and durable goods means that, at some level, the money transferred is being efficiently spent. Hence, the increased consumption of the observed households enhances their welfare, which means an immediate relief from poverty conditions. It should be highlighted that enhanced consumption due to the money transfers ameliorates households poverty adversities in the short run and also has effects in the long run. Such effects are related to childhood support in the sense that, if money transfers expenditures by the households are really focused in the right goods, it will improve households diet and consequently of their children. The consumption of goods related to education, health and food would present long run turnovers in the poverty cycle, as long as better nutritional status, health care, and education incentives were joined to improve the human capital of the children.